1984
DOI: 10.1128/jb.159.1.93-99.1984
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Tn10-dependent expression of the lamB gene in Escherichia coli

Abstract: Among TnlO insertions isolated in or near the malB region of Escherichia coli, one (zjb-729::TnlO) mapped between malK and lamB or late in malK and allowed MalT-independent expression of lamB. TnlO-dependent expression of a lamB-lacZ protein fusion was 25% of the expression of the fusion from the malK-lamB operon promoter in maiTh constitutive strains. The maltoporin content of a strain carrying this TnlO was about 20% that of a maiTh malB+ strain. Transport of maltose at concentrations of below 10-6 M was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…This is because of the presence of the relatively strong p out promoter in the IS10 elements, which gives rise to an antisense transcript that regulates the expression of Tn10 transposase (Halling et al, 1982;Simons et al, 1983). When Tn10 is appropriately inserted, p out can produce a stable transcript that may also contain the message for downstream chromosomal genes (Ciampi et al, 1982;Simons et al, 1983;Brass et al, 1984). Therefore, the localization of Tn10-8 just 26 bp upstream of leuO with the putative ribosomal-binding site (Shine-Dalgarno sequence) fully intact suggested that the phenotypes of the Tn10-8 insertion mutant could be caused by overproduction of LeuO protein instead of its elimination.…”
Section: Overexpression Of Leuo Results In Reduced Rpos Expressionmentioning
confidence: 99%
“…This is because of the presence of the relatively strong p out promoter in the IS10 elements, which gives rise to an antisense transcript that regulates the expression of Tn10 transposase (Halling et al, 1982;Simons et al, 1983). When Tn10 is appropriately inserted, p out can produce a stable transcript that may also contain the message for downstream chromosomal genes (Ciampi et al, 1982;Simons et al, 1983;Brass et al, 1984). Therefore, the localization of Tn10-8 just 26 bp upstream of leuO with the putative ribosomal-binding site (Shine-Dalgarno sequence) fully intact suggested that the phenotypes of the Tn10-8 insertion mutant could be caused by overproduction of LeuO protein instead of its elimination.…”
Section: Overexpression Of Leuo Results In Reduced Rpos Expressionmentioning
confidence: 99%
“…we replaced the malB region in these strains with the malB region from a strain (HS3140) that is AmalE444 malF+ malG+ malK+ lamB+ and has a TnWO transposon (zib-729::TnJO) closely linked to the malB genes (5). This was done by transducing 15 Mal+ revertants to Tcr with a P1 lysate grown on HS3140.…”
Section: Methodsmentioning
confidence: 99%
“…1. The malE254 mutation confers P1 of JB55-29; select Tcr, screen Mal-P1 of JB56-29 into JB105; select Tcr, screen Mal+ P1 of MM407 (lamB102 zjb-729::TnIO) P1 of SH205 (zah-735::TnlO AlacUI69) into Tcs isolates of JB104 through JB106 (still contain P10 of ;jb-729::TrlIO [9]) P1 of JB55-42; select Tcr, screen Mal+ P1 of JB55-42; select Tcr, screen Mal-P1 of JB56-42 into JB103; select Tc', screen Mal-…”
Section: Methodsmentioning
confidence: 99%
“…1). zjb-729::TnlO allows TnJO-dependent constitutive expression of lamB at a level that is 25% of the wild-type level (9). This low level of expression of lamB was an advantage for this study, since lactose permeation through the outer membrane is the rate-limiting step up to fairly high lactose concentrations (0.2 mM) for the overall uptake process in strains carrying zjb-729::TnJO (see below).…”
Section: Mitomycin Induction Of Jb288mentioning
confidence: 99%
See 1 more Smart Citation